A Comprehensive Analysis of Vitamin D Levels Based on Demographic Data at INMAS, Mohakhali (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Sunshine Gold, a crucial element, namely vitamin D, is essential for maintaining calcium homeostasis and promoting bone mineralization. Its deficiency has become a global health issue, particularly concerning in our country, affecting people from all socioeconomic and geographic backgrounds, especially females and children. Methods: 111 blood samples were investigated in the In-vitro Division of the Institute of Nuclear Medicine and Allied Sciences (INMAS) in Mohakhali, Dhaka from January to December 2024. Demographic and socio-economic impacts on vitamin D levels and their probable reasons are investigated through several statistical and mathematical analytics. Results: About 75.67% of people are deficient in vitamin D (